ALTERNATIVE DISPUTE RESOLUTION TO CHILDREN IN CONFLICT WITH THE LAW ACCORDING TO JINAYAT LAW IN NANGGROE ACEH DARUSSALAM (NAD) - Citra Anggun Puspita; Amelia Cohenta (Penelitian dan Pengembangan Ilmu, 2025)
This research aims to determine the age limit of children and efforts to protect children in conflict with the law in Nanggroe Aceh Darussalam. This research is descriptive normative legal research. The approaches used are case approach and statutory approach. The technique of collecting legal materials uses literature study by using juridical analysis techniques in the form of exposure to legal materials. Based on the results of research and discussion, the author concludes that the legal system in Indonesia oversees several forms of main law in its existence in order to realize dignified justice, customary law is a complementary law, as is the case in NAD which is part of the national legal system, in dealing with one another subject to regulations and jinayat law. The existence of customary criminal law in life adds to the diversity of law, so that society is more awake with all the arrangements that exist geographically and has implemented qanun as a law specifically against children in conflict with the law.